Microwave-assisted synthesis, computational studies and antibacterial/ anti-inflammatory activities of compounds based on coumarin-pyrazole hybrid - Chavan, Rakesh R. (R Soc Open Sci, 2018)
An efficient, high-yield and rapid synthesis of (E)-1,5-dimethyl-4-((2-((substituted-2-oxo-2H-chromen-4-yl)methoxy)naphthalen-1-yl)methyleneamino)-2-phenyl-1,2-dihydropyrazol-3-one derivatives (3a–3i) containing Schiff base structures under microwave-irradiation has been described. Schiff base is a potential target to discover anti-inflammatory chemotherapeutics, material science, catalysis and molecular magnetism. All the newly synthesized compounds (3a–3i) have been characterized by elemental analysis and spectroscopic techniques. The synthesized compounds (3a–3i) were evaluated for their antibacterial activity by agar-well diffusion method and anti-inflammatory activity by egg albumin denaturation method. The compounds (3e) and (3i) exhibit antibacterial effect with minimum inhibitory concentration (MIC) 0.78 µg ml(−1) and MIC 1.562 µg ml(−1) against Gram-positive Staphylococcus aureus bacterial strain compared with standard ciprofloxacin drug (MIC 6.25 µg ml(−1)). The compounds (3c) and (3f) exhibited an inhibition of heat-induced protein denaturation at the concentration (31.25 µg ml(−1)) as 53.65% and 67.27%, respectively, and these compounds are more active than standard aceclofenac drug (5.50%). Molecular docking study has been performed for all the synthesized compounds with S. aureus dihydropteroate synthetase and results obtained are quite promising.